Analisis Pengaruh Afiliasi Bisnis Terhadap Kinerja Perusahaan dan Saham Pada PT Sofyan Hotels, Tbk di Masa Covid-19 - En Najla, Aura Nabilat (TSARWAH, 2024)
The study aims to assess the impact of Business Affiliates, specifically Profitability Ratios, on the performance and stock prices of PT Sofyan Hotels, Tbk during the Covid-19 pandemic. Business affiliation serves as the independent variable (X), encompassing profitability ratios (X1) such as gross profit margin, net profit margin, return on investment, and return on equity. The dependent variables include (Y1) company performance indicators like sales revenue, net income after tax, and earnings per share, and (Y2) stock metrics such as earnings per share, price to book value, and price earnings ratio. Financial data spanning six years (2016-2021) for PT Sofyan Hotels, Tbk was analyzed using Partial Least Squares (PLS) with SmartPLS version 3.0 software. The first hypothesis (H1) posits that Profitability Ratios significantly impact company performance; the second hypothesis (H2) suggests that Profitability Ratios significantly affect stock performance; and the third hypothesis (H3) proposes that Company Performance significantly influences stock performance.